Bait-trap chip for accurate and ultrasensitive capture of living circulating tumor cells. (May 2023) - Jiang, Wenning; Han, Lulu; Li, Guorui; Yang, Ying; Shen, Qidong; Fan, Bo; Wang, Yuchao; Yu, Xiaomin; Sun, Yan; He, Shengxiu; Du, Huakun; Miao, Jian; et al.
Abstract: Accurate analysis of living circulating tumor cells (CTCs) plays a crucial role in cancer diagnosis and prognosis evaluation. However, it is still challenging to develop a facile method for accurate, sensitive, and broad-spectrum isolation of living CTCs. Herein, inspired by the filopodia-extending behavior and clustered surface-biomarker of living CTCs, we present a unique bait-trap chip to achieve accurate and ultrasensitive capture of living CTCs from peripheral blood. The bait-trap chip is designed with the integration of nanocage (NCage) structure and branched aptamers. The NCage structure could "trap" the extended filopodia of living CTCs and resist the adhesion of filopodia-inhibited apoptotic cells, thus realizing the accurate capture (∼95% accuracy) of living CTCs independent of complex instruments. Using an in-situ rolling circle amplification (RCA) method, branched aptamers were easily modified onto the NCage structure, and served as "baits" to enhance the multi-interactions between CTC biomarker and chips, leading to ultrasensitive (99%) and reversible cell capture performance. The bait-trap chip successfully detects living CTCs in broad-spectrum cancer patients and achieves high diagnostic sensitivity (100%) and specificity (86%) of early prostate cancer. Therefore, our bait-trap chip provides a facile, accurate, and ultrasensitive strategy for living CTC isolation in clinical. Statement of significance: A unique bait-trap chip integrated with precise nanocage structure and branched aptamers was developed for the accurate and ultrasensitive capture of living CTCs. Compared with the current CTC isolation methods that are unable to distinguish CTC viability, the nanocage structure could not only "trap" the extended-filopodia of living CTCs, but also resist the adhesion of filopodia-inhibited apoptotic cells, thus realizing the accurate capture of living CTCs. Additionally, benefiting from the "bait-trap" synergistic effects generated by aptamer modification and nanocage structure, our chip achieved ultrasensitive, reversible capture of living CTCs. Moreover, this work provided a facile strategy for living CTC isolation from the blood of patients with early-stage and advanced cancer, exhibiting high consistency with the pathological diagnosis. Graphical Abstract: Image, graphical abstract